The Effect of Training on Stride Parameters in a Cohort of 40 Two Year Old Racehorses. (June 2014) - Parkes, R; Pfau, T; Weller, R; Witte, T
Abstract : Introduction: The biomechanical effects of training on gait in the Thoroughbred are not fully understood. We aimed to assess the effect of training, surface and incline on stride parameters. Methods: 40 two‐year‐old Thoroughbred racehorses entering training were recruited and followed from December 2012 until September 2013. Gait analysis was performed at eleven time points by equipping each horse with an inertial measurement unit (IMU) with inbuilt GPS, mounted on the dorsum immediately caudal to the most caudal palpable lumbar dorsal spinous process. Horses were exercised as per their regular training regimen on a variety of training surfaces and inclines. Data were analysed using custom software written in Matlab (Mathworks, UK), and statistical analysis was performed using R (R Foundation for Statistical Computing, Austria). A linear mixed model was used, with horse as a random effect and weeks in training, training surface, curve and incline as fixed effects. Results: A total of 85, 497 strides at speeds of between 6.00 and 19.03 ms ‐1 were analysed. Stride length increased by 0.33 m ± 4.3 x 10 4 with each 1 ms ‐1 increase in velocity. Training causes a reduction in stride length of 0.004 ± 0.0001 m per week and an increase in stride frequency of 1.29 x 10 3 ± 4.1 x 10 5 per week. Shallow inclines, steep inclines and declines cause a decrease in stride length of 0.07 ± 0.003 m, 0.10 ± 0.005 m and 0.04 ± 0.004 m respectively. Turf and peat moss training surfaces caused an increase in stride length of 0.03 ± 0.004 m and 0.06 ± 0.007 m respectively. Conclusions: This study provides an insight into the effects of external factors on the gait of young Thoroughbreds in training. Ongoing research will further investigate these effects and interactions. Ethical Animal Research: The study was approved by the local ethics committee. Explicit owner informed consent for participation in this study is not stated.Sources of funding: Horserace Betting Levy Board.Competing interests: none.